3(2d+3)=4d+3

Simple and best practice solution for 3(2d+3)=4d+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2d+3)=4d+3 equation:


Simplifying
3(2d + 3) = 4d + 3

Reorder the terms:
3(3 + 2d) = 4d + 3
(3 * 3 + 2d * 3) = 4d + 3
(9 + 6d) = 4d + 3

Reorder the terms:
9 + 6d = 3 + 4d

Solving
9 + 6d = 3 + 4d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-4d' to each side of the equation.
9 + 6d + -4d = 3 + 4d + -4d

Combine like terms: 6d + -4d = 2d
9 + 2d = 3 + 4d + -4d

Combine like terms: 4d + -4d = 0
9 + 2d = 3 + 0
9 + 2d = 3

Add '-9' to each side of the equation.
9 + -9 + 2d = 3 + -9

Combine like terms: 9 + -9 = 0
0 + 2d = 3 + -9
2d = 3 + -9

Combine like terms: 3 + -9 = -6
2d = -6

Divide each side by '2'.
d = -3

Simplifying
d = -3

See similar equations:

| 0.5x+2.5=2x-3 | | -3+5x=4x+6 | | 4+6x=5x+8 | | 3x+10=19+2x | | 6x+6=-24-4x | | -6x-10=3x+44 | | -x+3=-15-7x | | (4x-5)*(2x-5)=105 | | h(x)=9x/(6x-11) | | 7a+2=26+3a | | 2ab+5ba+3ab= | | cx^2-(a^2+b^2)x+ab=o | | 2-4ln(x)=7 | | 2.2=6.1+y | | 0.65x+0.05(12-x)=0.10(-90) | | .065x+0.05(12-x)=0.10(-90) | | 88x^4/121x | | 6-3(4x-6)=-6 | | ln(x/y)-ln(10) | | ln(x/10*y) | | 2+7a=65 | | 5x-4=5(x-9) | | -4(x+8)=-44 | | p=a+3+c | | 5(w-4)=25 | | 4.1y=20.5 | | 10y-5=5y+5 | | 5b-6=8b | | 9x-9=40 | | -6x-14x=40 | | 5c-8c=21 | | 7a+2=26+39 |

Equations solver categories